Localization of the Spotify Website from English to Indonesian - Satyaningrum, Nisrina; Alfarisy, Fitri (Jurnal Komunikasi, 2024)
The rise of a digitally and globally integrated society has pushed global companies to adapt their products across various markets through GILT. Among the businesses that have successfully localized their platform for the Indonesian market is Spotify. Using a qualitative case study approach, this study examines the verbal and nonverbal components of the Premium, Support, Download, and Legal webpage localization of Spotify. The study identifies three core localization aspects: technical, content, and linguistic. It also highlights adjustments like price localization, payment methods, copywriting strategies, and the use of loanwords, target language equivalents, and naturalized terms. The analysis comes to the conclusion that due to internationalization and market localization, the Indonesian Spotify website closely mirrors the original, while also being localized for the target locale.